Taxonomia e variação geográfica das populações da centopeia Scolopendra viridicornis Newport, 1844 com a revisão de espécies e subespécies relacionadas (Chilopoda, Scolopendromorpha, Scolopendridae) - Souza, Emerson Marques de (2020)
The centipede species Scolopendra viridicornis Newport, 1844 has a wide distribution in Brazil and in some neighboring countries such as Bolivia, Paraguay and Argentina. It is the largest and most aggressive centipede in Brazil and known for causing serious accidents in humans. Currently,S. viridicornis inculdes the subspecies and S. v. viridicornis (nominal forms) and S. v. nigra Bücherl, 1940. In addition, two other taxa of the genus, S. spinipriva Bücherl, 1946 and S. pomacea minuscula Bücherl, 1946, present morphological characters very similar to S. viridicornis, suggesting possible cases of synonymy. Herein, we present a taxonomic revision of S. viridicornis including phonetically similar taxa based meristic characters, as well as linear and geometric morphometry. Our sample includes of 254 specimens from six Brazilian collections, as well as photographs of the type material of S. viridicornis nigra, S. spinipriva and S. pomacea minuscula. The geometric morphometry did not reveal variations allowing recognition of more then one entity among the specimens of our sample. Twenty eight phenotypic characters were observed, with 17 non-informative characters. In addition, meristic characters and linear morphometry corroborate the results of geometric morphometry, indicating that S. pomacea minuscula and S. viridicornis nigra represent junior synonyms of S. viridicornis. Regarding sexual dimorphism and distinction among life stages, we found no informative morphological characters regarding these parameters. Thus, all the examined taxa must be nested in a single species, whose valid name remains of S. viridicornis, by priority. An integrative study between molecular data and venom properties of S. viridicornis should help elucidating the relationships among the S. viridicornis populations and an ontogenetic development wil help understanding the stages of life within the genus.